A novel micro-nano composite structure on super-hydrophobic aluminum alloy surface and preparation method thereof

By constructing a spiral step structure on the surface of the aluminum alloy and performing low surface energy modification, combined with environmentally friendly etchant, the surface corrosion problem of aluminum alloy is solved, and superhydrophobic, corrosion-resistant and environmentally friendly effects are achieved.

CN116121753BActive Publication Date: 2025-05-02THE 724TH RESEARCH INSTITUTE OF CHINA STATE SHIPBUILDING CORP LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211443431.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-18
Publication Date
2025-05-02
Estimated Expiration
2042-11-18

AI Technical Summary

Technical Problem

Aluminum and aluminum alloys are prone to corrosion during use, especially in high humidity and high salt environments, resulting in shorter service life and safety hazards. The prior art uses strong acid etching method to prepare superhydrophobic surfaces, but there are problems of environmental pollution and uneven structural distribution.

Method used

A new micro-nano composite structure is adopted, composed of spiral stepped structures stacked and interlaced, and a uniform and stable superhydrophobic surface is prepared through low surface energy modification technology, combined with a mixed etchant of HCl, H2C2O4 and H2O2.

Benefits of technology

The superhydrophobicity of the aluminum alloy surface is achieved, the mechanical stability, anti-fouling and corrosion resistance of the material is improved, the production cost is reduced, and the pollution to the environment is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116121753B_ABST
    Figure CN116121753B_ABST
Patent Text Reader

Abstract

The invention discloses a novel micro-nano composite structure on a super-hydrophobic aluminum alloy surface and a preparation method thereof, and belongs to the technical field of surface modification of metal materials, wherein the novel micro-nano composite structure is compounded by overlapping staggered symbols of spiral staircases, wherein the spiral staircase length is 5 50 μm, the width is 1 6 μm, and the height is 500 nm 10 μm. The base material is etched by a simple and easy, low-cost chemical etching method, and the material after etching is modified by fluorosilane to obtain a super-hydrophobic aluminum alloy surface. The present invention can greatly improve the hydrophobicity, mechanical stability, antifouling performance and corrosion resistance of aluminum alloy materials, etc., and has practical significance for solving the problems such as easy corrosion of aluminum alloy materials in marine environments and poor stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material surface modification. Background Art

[0002] Aluminum and aluminum alloys have become indispensable engineering materials due to their advantages such as light weight, easy processing and casting, and good electrical conductivity. They are widely used in aerospace, shipbuilding, automobiles, electronic appliances and other fields. However, due to their high electrochemical activity on the surface, aluminum and aluminum alloys often face corrosion problems during use, especially in coastal areas. The high humidity and salt content in the air will accelerate the corrosion of aluminum alloys, shorten their service life, cause economic losses, and even cause safety accidents in severe cases. Therefore, the corrosion protection of aluminum and aluminum alloys has attracted widespread attention from researchers, and in-depth research has been carried out on this.

[0003] Inspired by the "lotus effect", methods for constructing super-hydrophobic aluminum and aluminum alloy surfaces to improve the corrosion resistance of the substrate are constantly enriched and developed. The principle is mainly to construct a micro-nano composite rough structure on the surface of aluminum and aluminum alloys and modify it with low surface energy materials, so that an air cushion layer is formed when the droplets contact the substrate, thereby directly reducing the contact between the corrosive medium in the droplets and the substrate material, and achieving a significant improvement in the corrosion resistance of the substrate. The more common chemical etching method usually uses strong acid as an etchant, supplemented by low surface material modification, to generate a super-hydrophobic hierarchical micro-nano composite structure on the aluminum and aluminum alloy substrate, thereby improving the corrosion resistance of the substrate. However, the large-scale use of strong acid is not environmentally friendly. In addition, when strong acid is used alone as an etchant, the surface roughness structure prepared often has uneven distribution, which will affect the super-hydrophobicity of the substrate surface and is not conducive to improving the corrosion resistance. Summary of the invention

[0004] In view of the above problems, the present invention provides a novel micro-nano composite structure on the surface of a super-hydrophobic aluminum alloy and a preparation method thereof.

[0005] The present invention proposes a novel micro-nano composite structure on a super-hydrophobic aluminum alloy surface, and the technical solution includes:

[0006] A novel micro-nano composite structure on the surface of a super-hydrophobic aluminum alloy is formed by stacking and interlacing spiral steps, wherein the spiral steps have a length of 5-50 μm, a width of 1-6 μm, and a height of 500 nm-10 μm.

[0007] The present invention also proposes a method for preparing the novel micro-nano composite structure on the surface of the super-hydrophobic aluminum alloy, comprising the following steps:

[0008] Step 1: The surface of the aluminum alloy substrate is sanded and mechanically polished, and then placed in a mixed etchant consisting of HCl, H2C2O4, and H2O2 solutions for surface etching to generate a novel micro-nano composite structure with a spiral staircase structure stacked and staggered on the surface;

[0009] Step 2: ultrasonically clean and dry the aluminum alloy substrate after etching in step 1, then place the entire or part of the aluminum alloy substrate in a fluorosilane-ethanol solution for low surface energy modification, and after drying, obtain a partial or entire super-hydrophobic aluminum alloy surface.

[0010] Furthermore, in the mixed etchant in step 1, the concentration of HCl is 1.5mol / L-2.5mol / L, the volume fraction is 45%-49%, the concentration of H2C2O4 is 0.01mol / L-0.05mol / L, the volume fraction is 2%-10%, and the concentration of H2O2 is 1.5mol / L-2.5mol / L, the volume fraction is 45%-49%. The surface etching treatment temperature is 5-30°C, and the etching treatment time is 20-60min.

[0011] Furthermore, in step 2, the fluorosilane is heptadecafluorodecyltriethoxysilane, the concentration of the fluorosilane-ethanol solution is 1.5-2.0wt%, the low surface energy modification time is 1-5h, the drying temperature is 50-150°C, and the drying treatment time is 1-3h.

[0012] The present invention provides a novel micro-nano composite structure on the surface of a super-hydrophobic aluminum alloy and a preparation method thereof. The structure has a uniform and stable morphology, has good adhesion to a substrate, and can achieve super-hydrophobicity on the surface in combination with low surface energy modification, which can effectively improve the mechanical stability, antifouling performance and corrosion resistance of the aluminum alloy substrate material. An organic weak acid and hydrogen peroxide are added to the etchant involved in the present invention, which can effectively improve the problems of difficult control of etching time and uneven etching structure, making the preparation process simple and controllable, reducing production costs, reducing the use of strong acids, and being more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a scanning electron microscope image of the micro-nano composite structure on the surface of the aluminum alloy after treatment in Example 1 of the present invention;

[0014] Figure 2 This is a schematic diagram of the contact angle of the aluminum alloy substrate surface after being treated in Example 1 of the present invention;

[0015] Figure 3 This is a graph showing the change in hydrophobicity of the aluminum alloy surface after multiple friction cycles after being treated in Example 1 of the present invention;

[0016] Figure 4The figure is a comparison of the antifouling performance of the surface of an untreated (a) aluminum alloy substrate and the surface of an aluminum alloy substrate treated in Example 1 of the present invention (b);

[0017] Figure 5 The polarization curves of the surface of the aluminum alloy substrate treated in Example 1 of the present invention after immersion for different times and the surface of the untreated aluminum alloy substrate are shown. DETAILED DESCRIPTION

[0018] The specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, so that the features and advantages of the present invention can be more easily understood by those skilled in the art, and the protection scope of the present invention can be more clearly defined.

[0019] Example 1

[0020] A novel micro-nano composite structure on the surface of a super-hydrophobic aluminum alloy, wherein the micro-nano structure is formed by stacking and interlacing spiral step structures with a step length of 5-50 μm, a width of 1-6 μm, and a height of 500 nm-10 μm; after low surface energy modification, the substrate surface exhibits super-hydrophobicity; has good mechanical stability; exhibits excellent anti-fouling effect; and can effectively improve the corrosion resistance of the aluminum alloy substrate.

[0021] A method for preparing a novel micro-nano composite structure on a super-hydrophobic aluminum alloy surface comprises the following steps:

[0022] Step 1: The surface of the aluminum alloy substrate is sanded with sandpaper and mechanically polished, and then washed and dried, and then placed in a mixed etchant solution of HCl, H2C2O4 and H2O2 with concentrations of 2 mol / L, 0.01 mol / L and 2 mol / L and volume fractions of 49%, 2% and 49%, respectively, and the surface is etched at 20°C for 30 minutes to generate a micro-nano composite structure with stacked and staggered spiral structures on its surface;

[0023] Step 2: The aluminum alloy substrate after etching in step 1 is immersed in a 2.0 wt % heptadecafluorodecyltriethoxysilane-ethanol solution for 1 hour, taken out and dried in an oven at 100° C. for 1.5 hours to obtain a micro-nano composite structured surface with super hydrophobic properties.

[0024] Surface morphology analysis: Field emission scanning electron microscopy was used to observe the morphology of the micro-nano composite structure on the surface of the aluminum alloy matrix, such as Figure 1 As shown, the morphology presents a stacked and staggered spiral step structure with a step length of 5-50μm, a width of 1-6μm, and a height of 500nm-10μm. The structure is evenly distributed on the surface.

[0025] Contact angle analysis: Use a contact angle meter to measure the contact angle of the substrate surface after low surface energy modification. Figure 2Observations showed that the static contact angle reached 159.13° and the rolling angle test was 3.0°, successfully endowing the aluminum alloy matrix material with excellent superhydrophobic properties.

[0026] Mechanical stability analysis: The mechanical stability of the super-hydrophobic surface of aluminum alloy was tested by sandpaper friction test. Figure 3 It can be found that with the increase in the number of sandpaper friction cycles, the contact angle of the aluminum alloy surface decreases, and the rolling angle shows an upward trend. When the number of sandpaper friction cycles reaches 20 times, the aluminum alloy surface still maintains excellent superhydrophobicity, showing the good mechanical stability of the surface.

[0027] Antifouling performance analysis: Industrial sand was selected as the pollution source, and the antifouling performance of the untreated aluminum alloy substrate surface and the treated aluminum alloy super-hydrophobic surface was tested. Figure 4 As shown in the figure, on the untreated aluminum alloy substrate surface, the pollutants will not leave the substrate surface as the water droplets fall, but spread on the substrate surface together with the water droplets, and the anti-fouling effect is poor; in contrast, on the super-hydrophobic aluminum alloy surface after surface treatment, when the droplets fall, the pollutants will roll down with the water droplets and leave the substrate surface, showing an excellent anti-fouling effect.

[0028] Corrosion resistance analysis: The corrosion resistance of the aluminum alloy substrate surface was tested using an electrochemical workstation. Sodium chloride solution was used to simulate seawater when the super-hydrophobic aluminum alloy substrate was immersed. The test analysis results are as follows: Figure 5 As shown in the figure, the corrosion current density of the untreated aluminum alloy substrate is 3.08×10 -5 A.cm -2 , corrosion potential is -0.80V, polarization resistance is 762.9Ω·cm 2 The corrosion current density of the treated super-hydrophobic aluminum alloy surface was reduced to 2.42×10 -8 A.cm -2 , which is about 3 orders of magnitude lower than that of aluminum alloy, the corrosion potential shifts to -0.42V, and the polarization resistance increases to 3.7×10 6 Ω·cm 2 The data show that the corrosion resistance of the superhydrophobic surface has been greatly improved; after immersion in simulated seawater for 20 days, the treated aluminum alloy surface still maintains a high corrosion potential (E corr ), lower corrosion current density (I corr ) and a larger polarization resistance (R p ), which shows that the aluminum alloy surface prepared by the present invention has good corrosion resistance and durability, can protect the aluminum alloy for a long time, and is beneficial to prolonging the service life of the aluminum alloy in a high-salt and high-humidity environment.

[0029] Example 2

[0030] A novel micro-nano composite structure on the surface of a super-hydrophobic aluminum alloy, wherein the micro-nano structure is formed by stacking and interlacing spiral step structures with a step length of 5-50 μm, a width of 1-6 μm, and a height of 500 nm-10 μm; after low surface energy modification, the substrate surface exhibits super-hydrophobicity; has good mechanical stability; exhibits excellent anti-fouling effect; and can effectively improve the corrosion resistance of the aluminum alloy substrate.

[0031] A method for preparing a novel micro-nano composite structure on a super-hydrophobic aluminum alloy surface comprises the following steps:

[0032] Step 1: The surface of the aluminum alloy substrate is sanded with sandpaper and mechanically polished, and then placed in a mixed etchant solution of HCl, H2C2O4 and H2O2 with concentrations of 2 mol / L, 0.05 mol / L and 2 mol / L and volume fractions of 48%, 3% and 49% respectively, and the surface is etched at 25°C for 25 minutes to generate a micro-nano composite structure with spiral structures stacked and staggered on its surface;

[0033] Step 2: The aluminum alloy substrate after etching in step 1 is immersed in a 1.8 wt % heptadecafluorodecyltriethoxysilane-ethanol solution for 2 hours, taken out and dried in an oven at 80° C. for 2 hours to obtain a micro-nano composite structured surface with super hydrophobic properties.

[0034] The morphology analysis, contact angle analysis, mechanical stability analysis, antifouling performance analysis and corrosion resistance performance analysis of the micro-nano composite structure on the surface of the aluminum alloy substrate prepared in this embodiment are basically the same as those in Example 1 and will not be repeated here.

[0035] Example 3

[0036] A novel micro-nano composite structure on the surface of a super-hydrophobic aluminum alloy, wherein the micro-nano structure is formed by stacking and interlacing spiral step structures with a step length of 5-50 μm, a width of 1-6 μm, and a height of 500 nm-10 μm; after low surface energy modification, the substrate surface exhibits super-hydrophobicity; has good mechanical stability; exhibits excellent anti-fouling effect; and can effectively improve the corrosion resistance of the aluminum alloy substrate.

[0037] A method for preparing a novel micro-nano composite structure on a super-hydrophobic aluminum alloy surface comprises the following steps:

[0038] Step 1: The surface of the aluminum alloy substrate is sanded with sandpaper and mechanically polished, and then placed in a mixed etchant solution of HCl, H2C2O4 and H2O2 with concentrations of 1.8 mol / L, 0.01 mol / L and 1.5 mol / L and volume fractions of 46%, 7% and 47%, respectively, and the surface is etched at 25°C for 20 minutes to generate a micro-nano composite structure with spiral structures stacked and staggered on its surface;

[0039] Step 2: The aluminum alloy substrate etched in step 1 is immersed in a 1.5 wt % heptadecafluorodecyltriethoxysilane-ethanol solution for 4 hours, taken out and dried in an oven at 120° C. for 1 hour to obtain a micro-nano composite structured surface with super hydrophobic properties.

[0040] The morphology analysis, contact angle analysis, mechanical stability analysis, antifouling performance analysis and corrosion resistance performance analysis of the micro-nano composite structure on the surface of the aluminum alloy substrate prepared in this embodiment are basically the same as those in Example 1 and will not be repeated here.

[0041] Example 4

[0042] A novel micro-nano composite structure on the surface of a super-hydrophobic aluminum alloy, wherein the micro-nano structure is formed by stacking and interlacing spiral step structures with a step length of 5-50 μm, a width of 1-6 μm, and a height of 500 nm-10 μm; after low surface energy modification, the substrate surface exhibits super-hydrophobicity; has good mechanical stability; exhibits excellent anti-fouling effect; and can effectively improve the corrosion resistance of the aluminum alloy substrate.

[0043] A method for preparing a novel micro-nano composite structure on a super-hydrophobic aluminum alloy surface comprises the following steps:

[0044] Step 1: The surface of the aluminum alloy substrate is sanded with sandpaper and mechanically polished, and then placed in a mixed etchant solution of HCl, H2C2O4 and H2O2 with concentrations of 1.8 mol / L, 0.02 mol / L and 2.0 mol / L and volume fractions of 45%, 6% and 49%, respectively, and the surface is etched at 10°C for 45 minutes to generate a micro-nano composite structure with stacked and staggered spiral structures on its surface;

[0045] Step 2: The aluminum alloy substrate etched in step 1 is immersed in a 1.8 wt % heptadecafluorodecyltriethoxysilane-ethanol solution for 1 hour, taken out and dried in an oven at 50° C. for 3 hours to obtain a micro-nano composite structured surface with super hydrophobic properties.

[0046] The morphology analysis, contact angle analysis, mechanical stability analysis, antifouling performance analysis and corrosion resistance performance analysis of the micro-nano composite structure on the surface of the aluminum alloy substrate prepared in this embodiment are basically the same as those in Example 1 and will not be repeated here.

[0047] Example 5

[0048] A novel micro-nano composite structure on the surface of a super-hydrophobic aluminum alloy, wherein the micro-nano structure is formed by stacking and interlacing spiral step structures with a step length of 5-50 μm, a width of 1-6 μm, and a height of 500 nm-10 μm; after low surface energy modification, the substrate surface exhibits super-hydrophobicity; has good mechanical stability; exhibits excellent anti-fouling effect; and can effectively improve the corrosion resistance of the aluminum alloy substrate.

[0049] A method for preparing a novel micro-nano composite structure on a super-hydrophobic aluminum alloy surface comprises the following steps:

[0050] Step 1: The surface of the aluminum alloy substrate is sanded with sandpaper and mechanically polished, and then placed in a mixed etchant solution of HCl, H2C2O4 and H2O2 with concentrations of 2 mol / L, 0.01 mol / L and 1.5 mol / L and volume fractions of 47%, 8% and 45%, respectively, and the surface is etched at 15°C for 40 minutes to generate a micro-nano composite structure with spiral structures stacked and staggered on its surface;

[0051] Step 2: The aluminum alloy substrate after etching in step 1 is immersed in a 1.5 wt % heptadecafluorodecyltriethoxysilane-ethanol solution for 3 hours, taken out and dried in an oven at 100° C. for 1 hour to obtain a micro-nano composite structured surface with super hydrophobic properties.

[0052] The morphology analysis, contact angle analysis, mechanical stability analysis, antifouling performance analysis and corrosion resistance performance analysis of the micro-nano composite structure on the surface of the aluminum alloy substrate prepared in this embodiment are basically the same as those in Example 1 and will not be repeated here.

[0053] The above description is only a preferred embodiment of the present invention, but the protection scope of the present invention is not limited thereto, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A novel micro-nano composite structure on the surface of super-hydrophobic aluminum alloy, characterized by: The novel micro-nano composite structure is formed by overlapping and staggered spiral steps, the length of the spiral step structure is 5-50μm, the width is 1-6μm, and the height is 500nm-10μm; the novel micro-nano composite structure is etched by a mixed etchant consisting of HCl, H2C2O4, and H2O2 solution; wherein the HCl concentration in the mixed etchant is 1.5mol / L-2.5mol / L, and the volume fraction is 45%-49%, the H2C2O4 concentration is 0.01mol / L-0.05mol / L, and the volume fraction is 2%-10%, and the H2O2 concentration is 1.5mol / L-2.5mol / L, and the volume fraction is 45%-49%.

2. A method for preparing a novel micro-nano composite structure on a super-hydrophobic aluminum alloy surface according to claim 1, characterized in that: The following steps are involved: Step 1: The surface of the aluminum alloy substrate is sanded and mechanically polished, and then placed in a mixed etchant consisting of HCl, H2C2O4, and H2O2 solutions for surface etching to form a new type of micro-nano composite structure with spiral staircase stacking and staggered layers on its surface; Step 2: ultrasonically clean and dry the aluminum alloy substrate after etching in step 1, then place the entire or part of the aluminum alloy substrate in a fluorosilane-ethanol solution for low surface energy modification, and after drying, obtain a partial or entire super-hydrophobic aluminum alloy surface.

3. The method for preparing a novel micro-nano composite structure on a super-hydrophobic aluminum alloy surface according to claim 2, characterized in that: The surface etching treatment temperature in step 1 is 5-30° C., and the etching treatment time is 20-60 min.

4. The method for preparing a novel micro-nano composite structure on a super-hydrophobic aluminum alloy surface according to claim 2, characterized in that: In step 2, the concentration of the fluorosilane-ethanol solution is 1.5-2.0 wt %, the low surface energy modification time is 1-5 h, the drying temperature is 50-150° C., and the drying treatment time is 1-3 h.

5. The method for preparing a novel micro-nano composite structure on a super-hydrophobic aluminum alloy surface according to claim 2 or 4, characterized in that: In step 2, the fluorosilane is heptadecafluorodecyltriethoxysilane.

Citation Information

Patent Citations

  • Superhydrophobic surface and method for forming same

    CN101448591A

  • Preparation method of titanium implant surface with micro-nano composite structure

    CN102912349A